Tuberculous osteomyelitis in condyle of mandible: A case report - Niranjala Mohad; Ashok Dabir; Jayesh Vahanwala; Mukul Padhye; Jayant Patwardhan (Elsevier, 2021)
Tuberculosis (TB) is a chronic infectious granulomatous disease caused by the air-borne bacillus Mycobacterium tuberculosis (M.tuberculosis, M.Tb), and less frequently by other bacterium in the M. tuberculosis complex (M. bovis, M.africanum).It has two forms pulmonary and secondary causing other kinds of TB, collectively denoted extra pulmonary tuberculosis (EPTB), constitutes 15% to 20% of all cases of TB among immunocompetent adults, and it accounts for more than 50% of the cases in human immunodeficiency virus (HIV) positive individuals.Maxillofacial manifestations of tuberculosis form nearly 10% of all extra pulmonary manifestations of the disease. Tubercular infection of mandible is a rare condition. Tuberculous involvement of mandibular condyle is even rarer. The clinical appearance of TB infection of the TMJ has been described as unspecific, resembling arthritis, osteomyelitis, cancer or any kind of chronic joint diseases. The only manifestation may be a localized painful swelling of the jaw. The presented case is of osteomyelitis of the mandibular condyle in a 12year old male patient for whom TB was later suspected.In this case report the importance of correct diagnosis is emphasized as Osteomyelitis of condyle has the risk of being easily missed, owing to its atypical signs, symptoms and radiographic appearance.